Peran guru dalam meningkatkan motivasi belajar dan keterampilan sosial siswa sekolah dasar pasca pandemi - Marwanti, Endah; Megawati, Ida; Anggreini, Dewi; Nugroho, Irfan Adi; Fantoro, Fajar Mur; Rohayati, Andang (Universitas Sarjanawiyata Tamansiswa, 2022)
The influence of the lack of student learning motivation will be related to learning outcomes. The diverse character of students makes social attitudes change due to the impact of technology. This study aims to find out how to increase students' learning motivation and social skills through the role of teachers after the COVID-19 pandemic. This study uses a qualitative type of research by using the principal as a key informant. For the research sample, the principal appointed several teachers and selected the students in order to achieve data validity. Data collection techniques using observation techniques followed by interview techniques are the main techniques in this study. This study uses documentation techniques to complement the results of observation and interview techniques. The data analysis used is data collection, data reduction, data presentation, and conclusion drawing. The results of this descriptive study indicate that: in increasing learning motivation in the learning process, the teacher relates it to the material and everyday life. This is done by utilizing several existing facilities such as the use of LCD in the form of videos, and images according to the material to be studied. To improve student's social skills, teachers implement them with teacher behavior and attitudes. The teacher as a facilitator helps make it easier for students to receive learning materials. The teacher acts as a guide for children to get used to applying good social skills in every activity. Teachers are good role models in interacting with others. Keywords: Learning Motivation; Social skill; Teacher’s Role